PENGARUH EFEKTIVITAS SMART ASN DAN TRANSFORMASI DIGITAL ORGANISASI TERHADAP REFORMASI BIROKRASI PADA ERA DISRUPSI TEKNOLOGI 4.0 DI DPMD KABUPATEN SUMEDANG - Eka Listiani (LPPM UNSAP, 2026)
The rapid development of disruptive technologies in the Industry 4.0 era requires government institutions to develop digitally competent civil servants and transform their organizational systems to support effective bureaucratic reform. This study aims to analyze the partial and simultaneous effects of Smart Civil Servant Effectiveness and Organizational Digital Transformation on Bureaucratic Reform at the Community and Village Empowerment Office (DPMD) of Sumedang Regency. This study employed a quantitative approach with an explanatory associative design. The research population consisted of 75 civil servants at DPMD Sumedang Regency. Questionnaires were distributed to the entire population, of which 60 valid responses were obtained and analyzed. Data were collected using a five-point Likert-scale questionnaire. The analysis included validity and reliability tests, descriptive statistics, classical assumption tests, multiple linear regression, partial tests, a simultaneous test, and the coefficient of determination. The results indicate that Smart Civil Servant Effectiveness has a positive and significant effect on Bureaucratic Reform, with a regression coefficient of 0.412. Organizational Digital Transformation also has a positive and significant effect on Bureaucratic Reform, with a regression coefficient of 0.365. Simultaneously, both independent variables significantly affect Bureaucratic Reform. The coefficient of determination of 0.684 shows that Smart Civil Servant Effectiveness and Organizational Digital Transformation explain 68.4% of the variation in Bureaucratic Reform, while the remaining 31.6% is explained by other variables outside the research model. The study concludes that successful bureaucratic reform requires an integrated strategy that combines digitally competent, adaptive, collaborative, and ethical civil servants with adequate digital infrastructure, integrated systems, supportive digital leadership, and an adaptive organizational culture.